Hepatoprotective Activity of Ethanol Extract of Notika Leaves (Archboldiodendron calosericeum (kobuski)) on Liver Function in Carbon Tetrachloride-induced Mice - Nuralifah, Nuralifah; Parawansah, Parawansah; Sida, Nurramadhani A.; Malina, Rachma; Arfan, Arfan (Majalah Obat Tradisional, 2023)
Notika leaves are traditional medicinal plants used as antimalarial medications by the Papuans. Notika leaf is an endemic plant with many benefits but has not been scientifically proven. Plasmodium falciparum is a species of malaria that damages up to 50% of red blood cells, and its schizogony process mainly occurs in the liver. This study aims to confirm the activity of the ethanolic extract of notika leaf in improving liver function by using an experimental pre and post-test-only control group design with five treatment groups of Wistar strain mice. The normal group was treated with 0.5% NaCMC, the negative group was treated with 0.5% NaCMC and Carbon Tetrachloride (CCl4), and the third, fourth, and fifth groups received extract with doses of 125 mg/kgBW, 250 mg/kgBW, and 500 mg/kgBW, respectively. The extract was administered for seven days and, on the eighth day, was induced with CCl4 intraperitoneally. The SGOT and SGPT levels in mice were measured using a 5010v5+ photometer, and liver histopathology was examined using HE (Hematoxylin-Eosin) dye. The SGPT levels in the normal, negative, third, fourth, and fifth groups were 20.6 U/L, 52.08 U/L, 32.8 U/L, 19.8 U/L, and 7.8 U/L, respectively. Meanwhile, the SGOT levels were 18 U/L, 54.2 U/L, 28.2 U/L, 17.8 U/L, and 7.4 U/L in the normal, negative, third, fourth, and fifth groups, respectively. Based on ANOVA analysis, the SGPT and SGOT levels of the mice liver-treated group with notika leaf extract show significant values of < 0.05. The extract exhibits hepatoprotective activity and liver histological characteristics that do not induce necrosis at a dose of 500 mg/kgBW.